(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Burnout among nurses has become an increasing concern in global healthcare. This study examines the perceptions and attitudes of nurses in Dubai, UAE, regarding burnout assessment and its implications for personal and professional well-being. A cross-sectional survey was conducted involving 100 nurses who were purposively selected. Data were analysed using simple frequency and percentage distribution. The findings indicated that a majority of nurses recognise burnout and support periodic assessments. The study recommends implementing structured burnout assessment and intervention programs in healthcare settings.